2020
DOI: 10.1186/s13195-020-00640-3
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term consequences of COVID-19 infections for the development of neurological disease

Abstract: Increasing evidence suggests that infection with Sars-CoV-2 causes neurological deficits in a substantial proportion of affected patients. While these symptoms arise acutely during the course of infection, less is known about the possible longterm consequences for the brain. Severely affected COVID-19 cases experience high levels of proinflammatory cytokines and acute respiratory dysfunction and often require assisted ventilation. All these factors have been suggested to cause cognitive decline. Pathogenetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
421
0
37

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(466 citation statements)
references
References 27 publications
8
421
0
37
Order By: Relevance
“…The underlying causes for these symptoms related to COVID-19 and the mechanisms involved in potential long-lasting impairments are currently not fully understood but are probably multifactorial. These factors include direct viral infection of the nervous system, the systemic inflammatory response to the virus, cerebrovascular ischemia due to endothelial dysfunction or severe coagulopathy, the ARDS presented in severe cases, the use of invasive ventilation and sedation along with side effects of drugs used to treat COVID-19, and peripheral organ dysfunction (see Figure 1; Sasannejad et al, 2019;Heneka et al, 2020;Ogier et al, 2020). SARS-CoV-2, similarly to other coronaviruses, shows certain neurotropism.…”
Section: Mechanisms Involved In Cognitive and Neuropsychiatric Manifementioning
confidence: 99%
“…The underlying causes for these symptoms related to COVID-19 and the mechanisms involved in potential long-lasting impairments are currently not fully understood but are probably multifactorial. These factors include direct viral infection of the nervous system, the systemic inflammatory response to the virus, cerebrovascular ischemia due to endothelial dysfunction or severe coagulopathy, the ARDS presented in severe cases, the use of invasive ventilation and sedation along with side effects of drugs used to treat COVID-19, and peripheral organ dysfunction (see Figure 1; Sasannejad et al, 2019;Heneka et al, 2020;Ogier et al, 2020). SARS-CoV-2, similarly to other coronaviruses, shows certain neurotropism.…”
Section: Mechanisms Involved In Cognitive and Neuropsychiatric Manifementioning
confidence: 99%
“…SARS-CoV-2 is a neuroinvasive virus capable of triggering a cytokine storm and hyperinflammation with potential effects on the central nervous system [ 7 ]. Such pathogenetical progress of the acute immune reaction, along with acute respiratory dysfunction, may cause the immediate and long-term consequences on cognitive and neuropsychological function [ 7 , 8 ]. Furthermore, such emerging infectious diseases and the responding measures (i.e., isolation, quarantine, and social distancing) have tremendously impacted on people’s lifestyles and aroused psychological distress of high level [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various parameters have been proposed to predict prognosis and outcomes among patients with COVID, including the neutrophil to lymphocyte ratio (NLR) (27)(28)(29)(30). A metanalysis of six studies involving 1,141 patients has demonstrated that an elevated NLR is associated with severe disease manifestation (28).…”
Section: Introductionmentioning
confidence: 99%